Changes in Carpal Alignment after Surgery for Thumb Carpometacarpal Osteoarthritis: Comparative Analysis of Trapeziectomy with Ligament Reconstruction and Tendon Interposition Arthroplasty and Arthrodesis - Komura, Shingo; Hirakawa, Akihiro; Hirose, Hitoshi; Kawaguchi, Atsushi; Ito, Yoshiki; Matsumoto, Kazu; Akiyama, Haruhiko (Journal of Wrist Surgery, 2025)
The scaphotrapezial–trapezoidal (STT) ligament complex is an important stabilizer of the proximal carpal row, and its disruption may cause carpal instability. We hypothesized that trapeziectomy with ligament reconstruction and tendon interposition (T + LRTI) has a higher risk of carpal alignment changes compared to thumb carpometacarpal arthrodesis. Thus, we investigated changes in carpal alignment after T + LRTI and arthrodesis.We retrospectively analyzed 22 wrists that underwent T + LRTI and 29 wrists that underwent arthrodesis. We measured the scapholunate angle (SLA), radiolunate angle (RLA), radioscaphoid angle (RSA), capitolunate angle (CLA), and carpal height ratio (CHR). We compared these parameters preoperatively and postoperatively in both groups and compared the parameters' changes (Δ) between the groups. Moreover, we analyzed correlations among carpal alignment parameters in each group.In the T + LRTI group, postoperative values decreased significantly in the RLA (preoperation to postoperation: 3.2 degrees to −1.7 degrees), RSA (58.0 to 52.3 degrees), and CHR (0.51 to 0.49 degrees), whereas postoperative values remained unchanged for the SLA (54.8 to 53.9 degrees) and CLA (−12.3 to −11.3 degrees). In the arthrodesis group, the postoperative values did not change significantly in the SLA (57.8 to 57.7 degrees), RLA (2.2 to 1.4 degrees), RSA (60.0 to 59.1 degrees), CLA (−11.5 to −10.2 degrees), and CHR (0.51 to 0.50). The ΔRLA was significantly lower in the T + LRTI group (−4.8 degrees) than in the arthrodesis group (−0.9 degrees). However, ΔRLA was positively correlated with ΔRSA in both groups. Postoperative dorsal intercalated segmental instability (DISI) developed in the T + LRTI group (n = 2) and the arthrodesis group (n = 1). Wrists with STT osteoarthritis after arthrodesis had greater reductions in the RLA and CHR than did wrists without STT osteoarthritis.T + LRTI significantly reduced the RLA, RSA, and CHR and posed a risk of DISI development, whereas arthrodesis did not significantly change carpal alignment. However, postoperative STT osteoarthritis could be associated with lunate extension, even during arthrodesis.
Keywords: thumb carpometacarpal osteoarthritis; trapeziectomy; arthrodesis; carpal alignment